Direct Costs of Parkinson’s disease in Brazil: A case study - Silva, Sávio Luís Oliveira da; Quelhas, Osvaldo Luiz Gonçalves; Neto, Julio Vieira; Leite, Marco Antônio Araújo; Leite, Marco Antônio Araújo; Mattos, João Dario; Cavaliere, Yasmin Ferreira (International Journal of Advanced Engineering Research and Science, 2021)
The lack of studies on the costs of Parkinson's disease in Brazil makes it difficult to predict the costs of treatment, making it impossible to assess the economic impact on the individual's life and on health systems. The objective of this research is to estimate the average annual cost of treating Parkinson's Disease in users of the Public Health System in the city of Niterói (RJ), based on the variables Direct Cost. Methods: The research followed a mixed methods design, with qualitative and quantitative data, obtained through interviews with a sample of 54 patients and analyzed through non-parametric tests due to the rejection of the normality of the numerical data sets obtained. Results: Eleven direct cost variables were identified in the literature with the treatment of the disease, with 84.5% of the total cost concentrated in four of them (Drugs, Hospitalizations, Home Care and Auxiliary Treatments). There is a difference between patient costs and degree of illness for the public and private categories. Groups did not differ from each other when these costs were related to gender, race, education level and current employment. The mean total annual cost was estimated at R14,293.6 (US2,904.8) and calculated from the mean and 95% confidence interval obtained. Conclusion: The estimation of individual costs with the treatment proved to be of fundamental importance for understanding the total costs, and justifies the importance of studies in this area, both for patients and for managers involved in health care.